2022
DOI: 10.3390/ijerph19074018
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gastrointestinal Diseases and Migraine

Abstract: Migraine is a common disease worldwide, and recent studies showed that the incidence of migraine was increased in patients with gastrointestinal (GI) diseases. In addition, preclinical evidence suggested a bidirectional relationship between the GI nervous system and the central nervous system called the gut–brain axis. This study aimed to determine the association between several high-prevalence GI diseases and migraine. Patients diagnosed with migraine or GI diseases were classified as the patient group at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…Migraine patients are at a higher risk of GI disorders, and this relationship is bidirectional, in agreement with the conception of the gut-brain-microbiota axis [ 96 ]. The prevalence of GI diseases was also higher in patients with medications for migraine, both for preventive and acute treatment.…”
Section: Dietary Nutrients May Reduce Gastrointestinal Functional Dis...supporting
confidence: 77%
“…Migraine patients are at a higher risk of GI disorders, and this relationship is bidirectional, in agreement with the conception of the gut-brain-microbiota axis [ 96 ]. The prevalence of GI diseases was also higher in patients with medications for migraine, both for preventive and acute treatment.…”
Section: Dietary Nutrients May Reduce Gastrointestinal Functional Dis...supporting
confidence: 77%
“…Strengths of this study included evaluation of the PK and safety effects in patients with migraine instead of healthy adults. Considering that patients with migraine are predisposed to gastrointestinal disorders (e.g., gastroparesis), 50,51 the PK of co‐administered atogepant and ubrogepant could have been altered due to this predisposition. The present study demonstrated that the PK of atogepant and ubrogepant in participants with a history of migraine were consistent with prior studies in heathy adults 32,38 .…”
Section: Discussionmentioning
confidence: 99%
“…When the mechanisms of both diseases are fully elucidated, then the pathophysiological relationship between them will be clearly understood. 60 4.3. Multiple Sclerosis.…”
Section: Gastrointestinal Diseasesmentioning
confidence: 99%
“…Also some GI symptoms including nausea may adversely affect migraine treatment. When the mechanisms of both diseases are fully elucidated, then the pathophysiological relationship between them will be clearly understood …”
Section: Migraine and Other Diseasesmentioning
confidence: 99%